An architecture and a roadmap for a detection method for debris flows and similar phenomena in rivers, using a wireless sensor network - Vargas-Fallas, Oscar (2013)
Debris flows and hiperconcentrated flows are very destructive phenomena that cause damage, injures and deaths to property and persons that live near rivers. Existing warning systems for these phenomena are based on fixed instrumentation on certain points of the river, or on remote, indirect measurements. As a result, the information that they provide is limited, neither real-time data about the advance of the flow trough the river, nor its velocity outside the fixed monitoring points is available. In this article, an architecture for a debris flows and hiperconcentrated flows detection method based on a wireless sensor network is proposed. This architecture is distributed and decentralized, since it does not depend on a central coordinator to decide on the presence or absence of the phenomenon. A roadmap for further research is also proposed, in order to solve challenges and problems that must be overcome in order to make possible an implementation of this architecture in a real world detection system.